2014
DOI: 10.1111/pce.12446
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses related to increased grain yield under drought in the first biotechnology‐derived drought‐tolerant maize

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 42 publications
6
75
0
Order By: Relevance
“…There have been copious reports of breakthroughs related to yield improvement and stress tolerance through biotechnology approaches, both in model species (Karaba et al, ; Kirst, Gabilly, Niyogi, Lemaux, & Melis, ; Kromdijk et al, ; Miwa, Takano, & Fujiwara, ; Sade et al, ; Van Camp, ), and in crops (Castiglioni et al, ; Nelson et al, ; Nuccio et al, ; Preuss et al, ; Rice et al, , Nemali et al, ). In many cases, there are reports of yield improvement with limited number of tested environments, and in no known cases, are there reports across multiple germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…There have been copious reports of breakthroughs related to yield improvement and stress tolerance through biotechnology approaches, both in model species (Karaba et al, ; Kirst, Gabilly, Niyogi, Lemaux, & Melis, ; Kromdijk et al, ; Miwa, Takano, & Fujiwara, ; Sade et al, ; Van Camp, ), and in crops (Castiglioni et al, ; Nelson et al, ; Nuccio et al, ; Preuss et al, ; Rice et al, , Nemali et al, ). In many cases, there are reports of yield improvement with limited number of tested environments, and in no known cases, are there reports across multiple germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Chang et al (2014) reported that no evidence suggested the cspB transgene in the corn hybrid evaluated impacted shoot or root architecture or yield when grown in moderate-to high-yield environments. Nemali et al (2014) reported the DT corn expressing the cspB transgene trait averaged 6% higher yields compared to the control under water-limited conditions, but there were no consistent results under well-watered conditions.…”
Section: Introductionmentioning
confidence: 94%
“…Monsanto’s “DroughtGuard” maize (MON87460) expressing Bacillus subtilis cold shock protein B (cspB) (Castiglioni et al, 2008) which produced 6% higher grain yield across years than the control (Monsanto hybrid NH6212) under water-limited conditions (Nemali et al, 2015) was cultivated on ≥50,000 ha in the United States during the first year after release (Marshall, 2014). New genes conferring drought and heat stress adaptation are being discovered and the experimental area sown to drought or heat stress tolerant crops containing transgene(s) is expected to grow as more countries become involved in the development and field testing of such crops.…”
Section: Synthesismentioning
confidence: 99%